Thrombophlebitis hiding under a KILT – case report on 40 years long-term follow-up of neonatal renal vein thrombosis - Stefan Lauener; Anne Bütikofer; Sandra Eigenheer; Robert Escher (BMC Pediatrics, 2019)
Abstract Background Neonatal renal vein thrombosis is a recognised cause of renal and inferior caval vein atresia (IVCA). However, the long-term impact of the condition is underrecognized with a high burden of morbidity for the patient, especially in adulthood. IVCA has been shown to be an independent risk factor for deep venous thrombosis (DVT) with a high risk of recurrence. The acronym KILT for kidney and inferior vena cava anomaly with leg thrombosis summarizes the pathological situation. Case presentation We present the case of a 40-year-old patient with pain in the right lower limb resulting from acute thrombophlebitis. No risk factors could be identified. His history was remarkable with two episodes of deep venous thrombosis first of the left, then the right leg 22 years earlier; at that time also, no risk factor was identified. Because of the idiopathic character of that thrombosis, the patient remained on long-term anticoagulation with phenprocoumon. The present thrombophlebitis occurred while the INR was not therapeutic in the preceding weeks. A CT with contrast showed atresia of the inferior vena cava and of the right kidney, and presence of numerous collaterals. A thorough medical history revealed a renal vein thrombosis as a neonate. Anticoagulation was intensified, and stent placement became necessary after a further 2 years. Discussion and conclusions KILT syndrome is a rare but underrecognized condition. Complications may arise in young adulthood only, and it is of prime importance to instruct parents of the pediatric patient of the possible consequences of renal vein thrombosis and to assure guidance from the treating physicians throughout adulthood. Diagnosis of IVCA is by CT with contrast or by MRI, and lifelong anticoagulation may be necessary. Since the KILT syndrome is widely underdiagnosed, we challenge the clinicians to keep it in mind when confronted with thrombophlebitis or thrombosis of the young, male and with no other identifiable risk factors for deep vein thrombosis.